Perlindungan Konsumen Pengguna Investasi Ilegal Vtube Berdasarkan Undang-Undang Nomor 21 Tahun 2011 tentang Otoritas Jasa Keuangan - Tamara Fransisca Jamal; Puti Priyana (Wajah Hukum, 2021)
The development of investment is currently growing rapidly due to technological advances, this progress has made it easier to invest with investment applications. This facility is misused by certain individuals who cause harm to the community due to illegal investment. In 2020, Indonesia was shocked by the corona virus that has spread throughout the world. This causes economic growth to decline. PT. Future View Tech launched an application called Vtube which is used by the public as an easy money-making tool. Vtube is an investment application declared as an illegal investment by the OJK. This study aims to determine the reasons behind the Vtube application called illegal investment and to determine the role of the OJK in providing legal protection to Vtube application users. The method used in this research is normative juridical. The result of this research is that Vtube is an illegal investment application because it carries out a business activity outside of its Industrial Business License (IUI), OJK's role in providing protection against illegal investment is regulated in Article 28 to Article 30 of the OJK Law and OJK provides preventive action. and repressive.